Olfactory response is a potential sign of consciousness: electroencephalogram findings - Wu, Wanchun; Xu, Chengwei; Liang, Qimei; Zheng, Xiaochun; Xiao, Qiuyi; Zhong, Haili; Chen, Na; Lan, Yue; Huang, Xiyan; Xie, Qiuyou (Frontiers in Neuroscience, 2023)
Objective This study aimed to explore whether olfactory response can be a sign of consciousness and represent higher cognitive processing in patients with disorders of consciousness (DoC) using clinical and electroencephalogram data. Methods Twenty-eight patients with DoC [13 vegetative states (VS)/unresponsive wakefulness syndrome (UWS) and 15 minimally conscious states (MCS)] were divided into two groups: the presence of olfactory response (ORES) group and the absence of olfactory response (N-ORES) group according to behavioral signs from different odors, i.e., vanillin, decanoic acid, and blank stimuli. We recorded an olfactory task-related electroencephalogram (EEG) and analyzed the relative power and functional connectivity at the whole-brain level in patients with DoC and healthy controls (HCs). After three months, the outcomes of DoC patients were followed up using the coma recovery scale-revised (CRS-R). Results A significant relationship was found between olfactory responses and the level of consciousness (χ2(1) = 6.892, p = 0.020). For olfactory EEG, N-ORES patients showed higher theta functional connectivity than ORES patients after stimulation with vanillin (p = 0.029; p = 0.027). Patients with N-ORES showed lower alpha and beta relative powers than HCs at the group level (p = 0.019; p = 0.033). After three months, 62.5% (10/16) of the ORES patients recovered consciousness compared to 16.7% (2/12) in the N-ORES group. The presence of olfactory response was significantly associated with an improvement in consciousness (χ2(1) = 5.882, p = 0.023). Conclusion Olfactory responses should be considered signs of consciousness. The differences in olfactory processing between DoC patients with and without olfactory responses may be a way to explore the neural correlates of olfactory consciousness in these patients. The olfactory response may help in the assessment of consciousness and may contribute to therapeutic orientation.